Pengembangan Instrumen Evaluasi Tes Two-Tier Multiple Choice Berbasis Literasi Sains Siswa Kelas VII Pada Tema Hujan Asam: (Development of Two-Tier Multiple Choice Test Evaluation Instruments Based on Science Literacy for Class VII Students on Acid Rain Theme) - Aulia Dinar Septiani; Sjaifuddin Sjaifuddin; Liska Berlian (BIODIK, 2022)
This research is motivated by the low scientific literacy skills in Indonesia based on the results of the 2015 PISA survey and the limitations of teachers in measuring students' scientific literacy skills so that they have not been developed optimally. The purpose of this study is to develop and determine the level of feasibility of the Two-Tier Multiple Choice test evaluation instrument based on scientific literacy on the theme of acid rain. The research method used is the research and development method with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluate) which in the development process is only at the Analyze, Design, Development, and Evaluate stages. The results of research and development in the form of a Two-Tier Multiple Choice test evaluation instrument based on scientific literacy on the theme of acid rain indicate that the product developed is very feasible based on assessments by material experts, evaluation experts, and three teachers with a total of 40 questions and gets a score the average is 97% based on material experts, 96% based on evaluation experts, 98% based on science teachers 1, 78% based on science teachers 2, and 99.8% based on science teachers 3. very feasible category with the overall average score of the validation has a percentage of 95%. Key words: Â Development research, Two-Tier Multiple Choice, Science Literacy skill, Acid rain Â  Abstrak. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan literasi sains di Indonesia berdasarkan hasil survey PISA tahun 2015 dan keterbatasan guru dalam mengukur kemampuan literasi sains siwa sehingga belum dikembangkan secara optimal. Adapun tujuan penelitian ini yaitu mengembangkan serta mengetahui tingkat kelayakan instrumen evaluasi tes Two-Tier Multiple Choice berbasis literasi sains pada tema hujan asam. Metode penelitian yang digunakan adalah metode penelitian dan pengembangan (research and development) dengan model pengembangan ADDIE (Analyze, Design, Development, Implementation, and Evaluate) yang dalam proses pengembangannya hanya pada tahapan Analyze, Design, Development, dan Evaluate. Hasil dari penelitian dan pengembangan berupa instrumen evaluasi tes Two-Tier Multiple Choice berbasis literasi sains pada tema hujan asam menunjukkan bahwa produk yang dikembangkan sangat layak berdasarkan penilaian oleh ahli materi, ahli evaluasi, dan tiga guru dengan jumlah soal sebanyak 40 butir soal dan mendapat skor rata-rata yaitu 97% berdasarkan ahli materi, 96% berdasarkan ahli evaluasi, 98% berdasarkan guru IPA 1, 78% berdasarkan guru IPA 2, dan 99,8% berdasarkan guru IPA 3. Kesimpulannya, dari 40 soal yang dikembangkan keseluruhan berada dalam kategori sangat layak dengan skor rata-rata keseluruhan validasi memiliki persentase sebesar 95%. Kata kunci: Penelitian pengembangan, Two-Tier Multiple Choice, Kemampuan literasi sains, hujan asam